Men in skintight pants? Changing body images of masculinity in between contemporary athletic and historically ethnic discourses - Haller, Melanie; Gerlsbeck, Silvia (Carmen Dexl (Ed.): De/Constructing Masculinity?, Palgrave)

Synthesis and Characterization of Catalytically Active Au Core─Pd Shell Nanoparticles Supported on Alumina - Feng, Yanyue; Schaefer, Andreas; Hellman, Anders; Di, Mengqiao; Härelind, Hanna; Bauer, Matthias; Carlsson, Per-Anders (Langmuir)
A two-step seeded-growth method was refined to synthesize Au@Pd core@shell nanoparticles with thin Pd shells, which were then deposited onto alumina to obtain a supported Au@Pd/Al2O3 catalyst active for prototypical CO oxidation. By the strict control of temperature and Pd/Au molar ratio and the use of l-ascorbic acid for making both Au cores and Pd shells, a 1.5 nm Pd layer is formed around the Au core, as evidenced by transmission electron microscopy and energy-dispersive spectroscopy. The core@shell structure and the Pd shell remain intact upon deposition onto alumina and after being used for CO oxidation, as revealed by additional X-ray diffraction and X-ray photoemission spectroscopy before and after the reaction. The Pd shell surface was characterized with in situ infrared (IR) spectroscopy using CO as a chemical probe during CO adsorption–desorption. The IR bands for CO ad-species on the Pd shell suggest that the shell exposes mostly low-index surfaces, likely Pd(111) as the majority facet. Generally, the IR bands are blue-shifted as compared to conventional Pd/alumina catalysts, which may be due to the different support materials for Pd, Au versus Al2O3, and/or less strain of the Pd shell. Frequencies obtained from density functional calculations suggest the latter to be significant. Further, the catalytic CO oxidation ignition-extinction processes were followed by in situ IR, which shows the common CO poisoning and kinetic behavior associated with competitive adsorption of CO and O2 that is typically observed for noble metal catalysts.
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Single-Layer T′ Nickelates: Synthesis of the La and Pr Members and Electronic Properties across the Rare-Earth Series - Wissel, Kerstin; Bernardini, Fabio; Oh, Heesu; Vasala, Sami; Schoch, Roland; Blaschkowski, Björn; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver; Cano, Andrés (Chemistry of Materials)
Understanding high-temperature unconventional superconductivity has become a long-lasting problem in which the cuprates stand as central reference materials. Given this impasse, the recent discovery of superconductivity in analogous nickelate thin films represents a fundamental breakthrough calling for the identification of additional materials in this class. In particular, thermodynamically more robust systems are required to “upgrade” nickelate superconductors from thin films to bulk samples. Here, we contribute in this direction by reporting the synthesis of the new single-layer T′ Pr2NiO3F compound, assessing this synthesis in relation to the only previous T′ nickelate La2NiO3F, and analyzing the electronic properties across the R2NiO3F series (R = La–Lu) via first-principles calculations. We find that these mixed anion systems have a comparatively high degree of stability and their synthesis enables a fine-tuning of their composition as inferred from their characterization. Furthermore, we find that these unprecedented square-planar nickelates hold great promise as prospective superconductors due to their exceptional electronic structure.
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Pseudo‐Octahedral Iron(II) Complexes with Near‐Degenerate Charge Transfer and Ligand Field States at the Franck‐Condon Geometry - Moll, Johannes; Naumann, Robert; Sorge, Lukas; Förster, Christoph; Gessner, Niklas; Burkhardt, Lukas; Ugur, Naz; Nuernberger, Patrick; Seidel, Wolfram; Ramanan, Charusheela; Bauer, Matthias; Heinze, Katja (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Fatshion - Haller, Melanie; Herrmann, Anja; Jun Kim, Tae; Kindinger, Evangelia; Mackert, Nina; Rose, Lotte; Schorb, Friedrich; Tolasch, Eva; Villa, Paula-Irene (Fat Studies. Ein Glossar, Bielefeld)

Synthesis and characterization of multichromophoric iron(II) complexes as novel photosensitizers - Dierks, Philipp

Hoffnung POP: Publizistisch-gestalterische Arbeits- und Lebensmodelle im postdigitalen Zeitalter unter Berücksichtigung der transformierenden Rahmenbedingungen. Drei beobachtend-teilnehmende Fallstudien vor dem Hintergrund einer gemeinsamen Forschungsperspektive. - Jacke, Christoph; Venker, Thomas; Roenneke, Stefanie; Godlewsky, Tanja (~Vibes – The IASPM D-A-CH Series. Volume No. 2: „Transformational POP: Transitions, Breaks, and Crises in Popular Music (Studies)”.)

Sustainability, Solutionism, and the Problem of Music. Kyle Devine interviewed by Christoph Jacke. - Jacke, Christoph; Devine, Kyle (~Vibes – The IASPM D-A-CH Series. Volume No. 2: „Transformational POP: Transitions, Breaks, and Crises in Popular Music (Studies)”.)

"Zwischen Hartz IV und Vollverbeamtung verläuft nur eine ganz dünne Grenze". Quo-Vadis Pop-Lehre? Eine journalistische Umfrage unter Lehrenden - Jacke, Christoph; Venker, Thomas (Kaput - Magazin für Insolvenz & Pop)

Situational Development of Low-Code Applications in Manufacturing Companies - Kirchhoff, Jonas; Weidmann, Nils; Sauer, Stefan; Engels, Gregor (Proceedings of the 25th International Conference on Model Driven Engineering Languages and Systems: Companion Proceedings)
Companies show an increasing interest in low-code development platforms to facilitate application development by domain experts without sophisticated software development knowledge. Thus, companies aim for a more efficient development of more effective applications since domain experts as so-called citizen developers are no longer limited by the availability and domain knowledge of trained software developers. Nevertheless, efficiency and effectiveness of application development is traditionally also largely influenced by the use of a suitable software development method. Domain experts are, however, not trained in software development methods. This introduces a risk of domain experts creating unusable applications or exceeding the designated time frame of a project (or both). In this paper, we therefore propose an initial version of a situational software development method which supports domain experts in manufacturing companies during the low-code development of applications. The method can be tailored based on situational factors, considering application requirements, features of the used low-code development platform, and characteristics of the development team. We also present feedback corroborating the usefulness of our method and future extension points based on expert interviews.

Silicon Photonic Radar Receiver IC for mm-Wave Large Aperture MIMO Radar Using Optical Clock Distribution - Kruse, Stephan; Gudyriev, Sergiy; Kneuper, Pascal; Schwabe, Tobias; Meinecke, Marc-Michael; Kurz, Heiko G.; Scheytt, J. Christoph (IEEE Microwave and Wireless Components Letters)

Richtiges und gutes Deutsch?

Postkarte - Schubert, Katrin (Im Nationalsozialismus. Praktiken – Kommunikation – Diskurse. Teil 2)

Putting Data Privacy Regulation into Action: The Differential Capabilities of Service Frontline Interfaces - Steinhoff, Lena; Martin, Kelly D. (Journal of Service Research)
Service frontline encounters between customers and service providers have been subject to fundamental changes in recent years. As two major change agents, technology infusion and data privacy regulations are inextricably linked and constitute a critical ethical and societal issue. Specifically, service frontlines—as represented by human or technological agents, or some hybrid form—rely on customer data for service provision, which subjects them to privacy regulations governing the collection, submission, access, and use of any customer data thus captured. However, scant research outlines the significant implications of evolving data privacy regulations for service frontline encounters. To advance knowledge in this domain, this research distills six key dimensions of global data privacy regulations (fairness, data limits, transparency, control, consent, and recourse). Employing an intelligences theoretical lens, the authors theorize how these dimensions might become differentially manifest across three service frontline interface types (human-based, technology-based, and hybrid). Carefully intersecting the need for varying intelligences across data privacy regulatory dimensions with the abilities of service frontline interfaces to harness each intelligence type, this study offers a novel conceptual framework that advances research and practice. Theoretical, managerial, and policy implications unfold from the proposed framework, which also can inform a future research agenda.
Keywords: Organizational Behavior and Human Resource Management; Sociology and Political Science; Information Systems

Exploring the Customer Journey of Voice Commerce: A Research Agenda - Böhm, Eva; Eggert, Andreas; Garnefeld, Ina; Holzmüller, Hartmut H.; Schaefers, Tobias; Steinhoff, Lena; Woisetschläger, David M. (Journal of Service Management Research)
Voice commerce creates unprecedented opportunities for consumers and vendor firms to interact, engage, and relate. With artificial intelligence-powered voice assistants, consumers can make technology-mediated purchases without using their tactile senses, which represents a new space for commercial interactions. Drawing on the customer journey as an organizing framework, this article proposes a structured research agenda, in an attempt to shed light on the bright side effects of voice commerce while also acknowledging concerns for consumer protection and society in general. Voice assistants can enhance every stage of the purchase journey, yet their use might have negative consequences for customer relationships. In the prepurchase stage, voice assistants can act as information curators or manipulators. In the purchase stage, voice assistants can adopt roles as shopping concierges or impediments. In the postpurchase and usage stage, voice assistants can become trusted relationship partners or hostile intruders in consumers’ lives.
Keywords: General Agricultural and Biological Sciences

Customer Engagement in International Markets - Steinhoff, Lena; Liu, Juanyi (Sunny); Li, Xiaoling; Palmatier, Robert W. (Journal of International Marketing)
Relationship marketing managers around the world actively try to stimulate customer engagement because of its performance-enhancing effects. Research insights into how to engage customers, such that they voluntarily contribute their resources to support companies’ marketing efforts, almost exclusively pertain to individual, domestic markets. However, the prerequisites of customer engagement strategies naturally differ across country-specific market environments. Therefore, the authors develop a conceptual, comprehensive battery of cultural, institutional, societal, and economic country-level contingency factors (CISE indicators) as well as between-country psychic distances on those indicators. A set of 11 high-level research propositions aims to enhance marketing researchers’ and managers’ understanding of the contingencies of international customer engagement strategy effectiveness and customer engagement's performance ramifications. The analysis reflects the richness and complexity of potential contingency effects across the four CISE categories and encourages empirical research on their separate and joint effects.
Keywords: Marketing; Business and International Management

Ni-based electrocatalysts for unconventional CO2 reduction reaction to formic acid - Lepre, Enrico; Heske, Julian; Nowakowski, Michal; Scoppola, Ernesto; Zizak, Ivo; Heil, Tobias; Kühne, Thomas D.; Antonietti, Markus; López-Salas, Nieves; Albero, Josep (Nano Energy)
Keywords: Electrical and Electronic Engineering; General Materials Science; Renewable Energy; Sustainability and the Environment

Chemotaxis and cross-diffusion models in complex environments: Models and analytic problems toward a multiscale vision. - Bellomo, Nicolas; Outada, Nisrine; Soler, Juan; Tao, Youshan; Winkler, Michael (Mathematical Models & Methods in Applied Sciences)

Global existence in reaction-diffusion systems with mass control under relaxed assumptions merely referring to cross-absorptiva effects. - Lankeit, Johannes; Winkler, Michael (Journal of Evolution Equations)

A double critical mass phenomenon in a no-flux-Dirichlet Keller-Segel system. - Fuhrmann, Jan; Lankeit, Johannes; Winkler, Michael (Journal de Mathématiques Pures et Appliquées)